Investigation of a Cluster of Candida albicans Invasive Candidiasis in a Neonatal Intensive Care Unit by Pulsed-Field Gel Electrophoresis - Jihene Ben Abdeljelil; Fatma Saghrouni; Imene Khammari; Soukeina Gheith; Akila Fathallah; Moncef Ben Said; Jalel Boukadida (The Scientific World Journal)
Nosocomial invasive candidiasis (IC) has emerged as a major problem in neonatal intensive care units (NICUs). We investigated herein the temporal clustering of six cases of neonatal IC due to Candida albicans in an NICU. Eighteen isolates obtained from the six neonates and two isolates from two health care workers (HCWs) working at the same unit and suffering from fingers’ onychomycosis were genotyped by electrophoretic karyotyping (EK) and restriction endonuclease analysis of genomic DNA by using Sfi I (PFGE-Sfi I). PFGE-Sfi I was more effective in discriminating between temporally related isolates. It showed that (i) both HCWs had specific strains excluding them as a source of infections in neonates. (ii) Isolates collected from three neonates were identical providing evidence of their clonal origin and the occurrence of a horizontal transmission of C. albicans in the unit. (iii) The three remaining neonates had specific strains confirming that the IC cases were coincidental. (iv) Microevolution occurred in one catheter-related candidemia case. Our results illustrate the relevance of the molecular approach to investigate suspected outbreaks in hospital surveys and the effectiveness of PFGE-Sfi I for typing of epidemiologically related C. albicans isolates.